2009
DOI: 10.1021/jp901987p
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions in Lyotropic Reverse Hexagonal Liquid Crystals: A Dielectric Spectroscopy Study

Abstract: A dielectric study of reverse hexagonal mesophases (HII) is presented. Conducted in the frequency range 0.01-1 MHz and temperature range 293 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 41 publications
(84 reference statements)
2
53
0
Order By: Relevance
“…Structural flexibility and stability is essential for a drug delivery system and tuning its physical properties (such as viscosity) and composition. Dielectric spectroscopy analysis of this system showed a critical temperature, T 0 = 307 K, related to the dehydration of the GMO head groups [26]. Effectively, this represented a breakdown of the interfacial layer of water.…”
Section: H II Mesophase Composed Of Gmo/triglyceride/watermentioning
confidence: 91%
See 3 more Smart Citations
“…Structural flexibility and stability is essential for a drug delivery system and tuning its physical properties (such as viscosity) and composition. Dielectric spectroscopy analysis of this system showed a critical temperature, T 0 = 307 K, related to the dehydration of the GMO head groups [26]. Effectively, this represented a breakdown of the interfacial layer of water.…”
Section: H II Mesophase Composed Of Gmo/triglyceride/watermentioning
confidence: 91%
“…In addition, it was shown that phosphatidylcholine (PC) can be embedded into the ternary GMO/TAG/water system [23][24][25][26]. PC was incorporated into the ternary mesophases, as it is known that phospholipid-based structures possess relatively high thermal stability, and enhance transdermal drug permeation [27][28][29] and transmembrane transport across the digestive tract [30,31].…”
Section: H II Mesophase Composed Of Gmo/triglyceride/watermentioning
confidence: 99%
See 2 more Smart Citations
“…This enabled expanding conditions to obtain stable H II mesophases at room temperature. In addition, it was shown that phosphatidylcholine (PC) can be embedded into the ternary GMO -TAG -water system (Ben Ishai et al, 2009 ;Libster et al, 2007Libster et al, , 2008Libster et al, , 2009a. PC was incorporated into the ternary mesophases because it is known that phospholipid -based structures possess relatively high thermal stability and enhance transdermal drug permeation (Kurosaki et al, 1991 ;Touitou et al, 1994 ;Spernath and Aserin, 2006 ) and transmembrane transport across the digestive tract (Brondsted et al, 1995 ;Liu et al, 1999 ).…”
Section: H II Mesophase Composed Of Gmo -Triglyceride-water As Drug Dmentioning
confidence: 99%